Investigation of salt intrusion condition in the Belat Estuary - Gisen, J. I. A.; Siti Syuhaida, Adnan; Ahmad Amirul Faiz, Ahmad Tajudin; Tian, Xian Chan (EDP Sciences, 2018)
Awareness on salt intrusion problem is still lacking in Malaysia due to high precipitation in the region. However, the El-Nino phenomenon that occurred recently has caused extremely low fresh water discharge in the Kuantan River which allowed the sea water to intrude further into its water intake region. Consequently, the Belat River may become potential water resources alternative to build new water intake station for the water supply in the Kuantan River Basin. The aims of this study are to: 1) investigate the salinity distribution in the Belat Estuary; 2) evaluate the applicability of the 1-D analytical salt intrusion solution; 3) determine the calibration parameters in the salt intrusion model. Salt intrusion measurements was conducted during the dry season at spring tide when the fresh water discharge is the minimum. Collection of data such as hydrological data, river cross section and salinity were collected to be used in the salt intrusion analysis. The results obtained show good agreement between the simulated and observed salinity distribution in the estuary with low RMSE and high NSE values. This indicates that the model is reliable and can become an important tool for water manager in conducting salt intrusion study for this area.